Root form and morphology of human permanent maxillary first premolars of an Indo-Dravidian population based in southern India: An in vitro study - Jeyaraman Venkataraman Karunakaran; Anbarasi Kaliyaperumal; Ragavendran Nagappan; Senthil Kumar Swaminathan; Kaneesh Karthik Arthanari; Leo Sujith Samuel (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this study was to analyze root form and morphology of human maxillary first permanent premolars of an Indo-Dravidian population from southern India. Materials and Methods: Eight hundred and twenty-two maxillary first permanent premolars were cleansed and stored appropriately. Morphology and root form analysed, segregated into Groups (Gps): Gp I, Gp II, and Gp III, and later divided into subgroups (SGs) based on specific criteria. Gp I was divided into two SGs: SG A (minimal or absence of grooving in the root) (n = 252) and SG B (clear and defined longitudinal groove in the root) (n = 104), and Gp II was divided into SG C (roots dividing in coronal one-third) (n = 154), SG D (roots dividing in the middle one-third) (n = 158), and SG E (roots dividing in the apical one third) (n = 138). Gp III consisted of only one SG F (teeth with three roots) (n = 16). The groups were analyzed separately, their external root form and morphology were recorded. Root form was analyzed, and results were tabulated. This study was compared with other studies and statistically analyzed. Results: Gp II was common with an incidence of 54.74%. Gp I was the next most common with an incidence of 43.3%. Gp III was the least common with an incidence of 1.94%. The number and distribution of roots was also computed. Six types of root form were identified (Type [Ty] A = 30.65%, Ty B = 12.65%, Ty C = 18.73%, Ty D = 19.22%, Ty E = 16.78%, and Ty F = 1.94%). Conclusion: Awareness and assessment of root form, number preoperatively with regard to specific populations before initiation will pave way for successful outcome of therapy.